Analisis Power Budget pada Jaringan Komunikasi Jarak Jauh Menggunakan SMF 28 - Sri Danaryani (Politeknik Negeri Batam, 2018)
The fourth generation of optical fibers is wavelength division multiplexing (DWDM), where several wavelengths propagate in a single optical fiber. This technique strongly supports broadband communication that is currently being developed. An optical amplifier (EDFA) is required for transmitted information to be received at the appropriate distance limits. The problem, where EDFA should be located and how to overcome the chromatic dispersion of signals occurs, especially on remote communications using SMF 28. The power budget analysis starts from the calculation of the distance between the amplifier and the strengthening of EDFA using the solution wave equation, where the large dispersion of chromatic fiber and the desired range becomes the determinant of the optical amplifier. Case study for 200 km of communication distance need three amplifiers with a space of about 80km. When a 1 GHz bandwidth is converted to 10 GHz, OSNR on each amplifier will decrease by 10 dB.